2013
DOI: 10.3906/elk-1108-8
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of transient processes on overvoltage in electric transmission lines using ATP-EMTP

Abstract: Abstract:In this paper, the mathematical modeling and simulation of electromagnetic transient processes is considered, which is of vital importance for examining the overvoltage phenomenon of power transmission systems. In the mathematical models of the AC power transmission systems that contain a power source, the power transformer, transmission line,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…In [2], mathematical models of two -and three-wire alternating-current transmission lines are developed, with the help of which different nature of transient processes is analysed using the software complex АТР-ЕМТР.…”
Section: Analysis Of Recent Researchmentioning
confidence: 99%
“…In [2], mathematical models of two -and three-wire alternating-current transmission lines are developed, with the help of which different nature of transient processes is analysed using the software complex АТР-ЕМТР.…”
Section: Analysis Of Recent Researchmentioning
confidence: 99%
“…In repetitive, severe cases TOV can lead to loss of life of plant [4][5][6][7][8][9][10][11][12][13][14]. The dedicated research from Ketabi [5] has shown a new approach that assists power system restoration planning with regards to control of temporary over-voltages mainly caused by transformer energisation.…”
Section: Introductionmentioning
confidence: 99%
“…These research findings are also in line with the research outcomes from Huang et.al. [13] and Nayir [14].…”
Section: Introductionmentioning
confidence: 99%
“…Динамические расчеты процессов в энергосетях проводятся также с помощью специализированных пакетов [Nayir, 2013]. В работе численные результаты по резонансам и переходным явлениям были получены с использованием ATP -свободной версии пакета динамического моделирования электрических процессов EMTP (Electromagnetic Transients Program).…”
Section: Introductionunclassified